Fibroadenoma of bilateral axillary ectopic breast tissue: A rare case report based on Orem's Self Care theory - Hülya Erbaba1; Gül Pinar2 (Archives of Nursing Practice and Care - Peertechz Publications, 2019)
Introduction: Ectopic Breast Tissue (EBT) is still a condition seen as sporadic (2-5%), and it is often delayed and ignored due to lack of awareness, whereas it may be exposed to malignant diseases. it must be always kept in mind for differential diagnosis of an EBT. We think that this case report is important because EBT associated with fi bro-adenoma is a quiet rare condition. Method: A 41-year-old female who has just given birth presented in bilateral axillary EBT with fi broadenoma. In order to present the nursing management to our case during hospitalization, Orem's (2001) self-care defi cit theory and North American Nursing Diagnosis Association (NANDA) classifi cation system were used.